Minutes of the 46th Meeting of BRAC University Academic Council (AC) - Academic Council, BRAC University (Vice Chancellor's Office, BRAC University, 2013)
1. Confirmation of Minutes of the 45th Meeting of the Academic Council. 2. Review of the progress and implementation of decisions of the 45th Meeting of the Academic Council. 3. Approval of the results of the students at the end of Fall 2011 Semester. 4. Proposal for changing the sequence of Micro and Marco Economic Courses in ESS and renumbering a course. 5. Research Proposal Review Committee. 6. Policy on Course Drop and Course Replacement. 7. Continuation of studies beyond 3rd time probations. 8. Update on the 8th Convocation. 9. Update on Admission Test. 10. Review of Expulsion Order of Ms. Farhana Alam. (ID# 07104027). 11. Miscellaneous: 11.1 Changing course code for Microbiology. 11.2 Approval of B. Sc in ECE program. 11.3 Appeal for continuation of studies. 11.4 Appeal for additional time for submission of Internship Report. 11.5 Appeal for continuation of study after a long break. 11.6 Appeal for continuation of study. 11.7 Incentive for Scholarship. 11.8 Eligibility of GED candidates for Admission in Undergraduate Courses.